2013
DOI: 10.1039/c3ob41498a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nitric oxide probes with fluorescence lifetime sensitivity

Abstract: We present the rationale, synthesis and evaluation of the first activatable fluorescent probe that utilizes fluorescence lifetime change for detection of nitric oxide. The new probe DAP-LT1 features a near-infrared polymethine skeleton with diaminobenzene functionality incorporated into the meso-position. The probe is partially quenched, and upon reaction with a nitric oxide shows an increase in the fluorescence lifetime from 1.08 ns to 1.24 ns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In the last decade work in the NIR technology opened a variety of new ways in industrial, scientific, military and medical applications with new optical devices, 39, 40, 92 imaging techniques 41, 42 contrast agents, 43, 44 and sensors. 45, 46 As a result of advances of new technology, a diverse set of photoluminescent compounds, emitting in the NIR region from small molecules to nanoparticles and larger aggregates, has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade work in the NIR technology opened a variety of new ways in industrial, scientific, military and medical applications with new optical devices, 39, 40, 92 imaging techniques 41, 42 contrast agents, 43, 44 and sensors. 45, 46 As a result of advances of new technology, a diverse set of photoluminescent compounds, emitting in the NIR region from small molecules to nanoparticles and larger aggregates, has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…A range of Mg 2+ lifetime probes has also been tested, but again without imaging (Szmacinski and Lakowicz, 1996). However, phosphate ions have been mapped in living cells using FLIM (Paredes et al, 2013), and nitric oxide lifetime probes have been reported, but without use in FLIM as yet (Zhegalova et al, 2013).…”
Section: Flim To Map Ion Concentrationsmentioning
confidence: 97%
“…1 (11). Isothiocyanatobenzene (0.20 mL, 0.23 mmol) and EDC (0.56 g, 2.9 mmol) were added to a stirred solution of N 1 -methyl-4-(4,4,5,5tetramethyl-1,3,2-dioxaborolan-2-yl)benzene-1,2-diamine ( 15) 56 in dry THF (16 mL) at rt. The mixture was heated to 50 °C for 16 h. The mixture was concentrated and the residue was partitioned between water (30 mL) and EtOAc (30 mL).…”
Section: -Chloro-n-(cyclopropylmethyl)-3-(1h-indazol-5-yl)imidazo[12b...mentioning
confidence: 99%